2017
DOI: 10.3791/55622
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of Surfactants from Atmospheric Aerosols

Abstract: Surface-active compounds, or surfactants, present in atmospheric aerosols are expected to play important roles in the formation of liquid water clouds in the Earth's atmosphere, a central process in meteorology, hydrology, and for the climate system. But because specific extraction and characterization of these compounds have been lacking for decades, very little is known on their identity, properties, mode of action and origins, thus preventing the full understanding of cloud formation and its potential links… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 31 publications
(55 reference statements)
1
23
0
Order By: Relevance
“…18 All this supported the validity of our results and indicated that amphiphilic surfactants are present in sub-micron aerosol particles in many different regions of Europe. As in previous works, 12,20 the surfactants extracted from the samples were divided into three ionic types: anionic, cationic and non-ionic surfactants. In all the samples studied in this work, anionic and non-ionic surfactants largely dominated over cationic ones, the latter being detected only in a few occurrences and at very small concentrations (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 All this supported the validity of our results and indicated that amphiphilic surfactants are present in sub-micron aerosol particles in many different regions of Europe. As in previous works, 12,20 the surfactants extracted from the samples were divided into three ionic types: anionic, cationic and non-ionic surfactants. In all the samples studied in this work, anionic and non-ionic surfactants largely dominated over cationic ones, the latter being detected only in a few occurrences and at very small concentrations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Over the years we have developed analytical methods to extract and characterize specifically amphiphilic surfactants in atmospheric aerosols. [11][12][19][20] With them, the presence of such compounds in atmospheric PM 11,19,21 and PM 12 aerosols was established. More recently, the selective extraction was applied to PM collected on a cascade impactor and evidenced the presence of amphiphilic surfactants throughout the entire size range, including sub-micron ones.…”
Section: Mostly Becausementioning
confidence: 99%
“…Surface active organic species (surfactants) are frequently found in atmospheric aerosols from many different regions and environments (e.g. Gérard et al, 2016;Petters and Petters, 2016;Nozière et al, 2017;Kroflič et al, 2018;Gérard et al, 2019). In liquid aerosol mixtures, such as aqueous droplets, surfactants can adsorb at the interfaces, lowering the surface tension and inducing concentration gradients between the droplet surface and bulk compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Ions compete for the adsorption sites at the micellar surface depending on their ability to form contact-pair or solventseparated pairs (Collins 1997;Vlachy et al 2008;Kunz 2009;Salis and Ninham 2014). Aqueous droplets formed from atmospheric aerosols typically comprise multicomponent solutions of inorganic salts and surfactants (Gérard et al 2016;Nozière et al 2017;Gérard et al 2019) and modeling of the micellization process in these systems is therefore not straightforward. For example, it has been experimentally determined by changing the relative humidity around levitated droplets comprising atmospheric fatty acids/fatty acid salts, that these surfactants can form complex tridimensional nanostructures including hexagonal and cubic close-packed arrangements of spherical and cylindrical micelles into bilayer stacks (Pfrang et al 2017).…”
Section: Introductionmentioning
confidence: 99%